Opportunities for Transdisciplinary Science to Mitigate Biosecurity Risks From the Intersectionality of Illegal Wildlife Trade With Emerging Zoonotic Pathogens - Aguirre, A. Alonso; Gore, Meredith L.; Kammer-Kerwick, Matt; Curtin, Kevin M.; Heyns, Andries; Preiser, Wolfgang; Shelley, Louise I. (Frontiers in Ecology and Evolution, 2021)
Existing collaborations among public health practitioners, veterinarians and ecologists do not sufficiently consider illegal wildlife trade in their surveillance, biosafety, and security (SB&S) efforts even though the risks to health and biodiversity from these threats are significant. We use the case of the novel coronavirus SARS-CoV-2 to illustrate an extreme case of risks posed by existing gaps in understanding the intersectionality of the illegal wildlife trade and zoonotic disease transmission. We argue for more integrative decision-making using the One Health approach. Opportunities abound for new avenues for policy and programmatic-relevant research in this integrative space, such as combining on-the-ground monitoring of health and environmental conditions with an understanding of the dynamics of illicit wildlife trade. We advocate for (1) a surveillance sample management system for enhanced diagnostic efficiency in collaboration with in-country partners that will establish or link to existing surveillance networks, outbreak analysis, and surveillance strategies; (2) novel analytical tools and decision support models that can improve local livelihoods by addressing monitoring, detection, prevention, interdiction, and remediation; (3) enhanced capacity to promote joint SB&S efforts that will encourage improved human and animal health, timely reporting, emerging disease detection, and outbreak response; and, (4) enhanced monitoring of illicit wildlife trade and its supply chains. By involving participants at all levels and sectors we can encourage policies that improve environmental conditions from the local to the regional levels.